2020
DOI: 10.1371/journal.pntd.0008150
|View full text |Cite
|
Sign up to set email alerts
|

Identification of anisomycin, prodigiosin and obatoclax as compounds with broad-spectrum anti-parasitic activity

Abstract: Parasitic infections are a major source of human suffering, mortality, and economic loss, but drug development for these diseases has been stymied by the significant expense involved in bringing a drug though clinical trials and to market. Identification of single compounds active against multiple parasitic pathogens could improve the economic incentives for drug development as well as simplifying treatment regimens. We recently performed a screen of repurposed compounds against the protozoan parasite Entamoeb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 74 publications
1
11
0
Order By: Relevance
“…Obatoclax displayed remarkable trypanocidal activity against the epimastigotes of T. cruzi ; however, its effectiveness against the intracellular forms of T. cruzi was slightly lower than that of the other molecules assayed. This is consistent with the results recently reported by Ehrenkaufer et al, who demonstrated that Obatoclax had remarkable activities against Entamoeba , Giardia , and Trypanosoma brucei , with IC 50 values of 0.5, 0.9, and 0.04 µM, respectively [ 34 ]. Here, we provide the effectiveness data of this compound in T. cruzi .…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Obatoclax displayed remarkable trypanocidal activity against the epimastigotes of T. cruzi ; however, its effectiveness against the intracellular forms of T. cruzi was slightly lower than that of the other molecules assayed. This is consistent with the results recently reported by Ehrenkaufer et al, who demonstrated that Obatoclax had remarkable activities against Entamoeba , Giardia , and Trypanosoma brucei , with IC 50 values of 0.5, 0.9, and 0.04 µM, respectively [ 34 ]. Here, we provide the effectiveness data of this compound in T. cruzi .…”
Section: Discussionsupporting
confidence: 92%
“…Therefore, they should be, in principle, resistant to Obatoclax unless the mode of action of Obatoclax involves some more targets than the inhibition of this apoptotic regulator. Ehrenkaufer et al [ 34 ] reported that other Bcl-2 inhibitors such as venetoclax, navitoclax, A-1331852, A-1210477, and S63845 do not have an effect on the viability of different parasites, subsequently suggesting that a different mechanism of action should be investigated. Their results clearly indicated that Obatoclax most likely kills the parasites through a BCL-2-independent mechanism.…”
Section: Discussionmentioning
confidence: 99%
“…Of the 11 compounds that were not part of a larger structural class, anisomycin had been previously reported in other screens to have broad-spectrum anti-parasitic activity in at least 3 other parasite species ( Ehrenkaufer et al, 2020 ; Sears and O'Hare, 1988 ). Anisomycin is proposed to inhibit protein synthesis specifically in eukaryotic cells, blocking peptide bond formation on eukaryotic ribosomes ( Jimenez and Vázquez, 1979 ).…”
Section: Resultsmentioning
confidence: 99%
“…In addition, the most effective combination that inhibited the parasite growth with limited cytotoxicity was 17.6% Diclofenaco-lepori and 82.4% atorvastatin [84]. Another study reported low EC 50 values for prodigiosin (2.2 µM) and obatoclax (0.5 µM) against A. castellanii trophozoites [85].…”
Section: Improvements In Existing Drugsmentioning
confidence: 99%